Effect of forging on the oxidation behavior of β-solidifying high Nb-containing TiAl alloy - Gengwu Ge; Laiqi Zhang; Yongfeng Liang; Junpin Lin (Journal of Materials Research and Technology)
This study focuses on the oxidation behavior of TiAl alloys containing only γ and β/B2 phases, and investigates the oxidation behavior of the as-cast and as-forged alloys at different temperatures. The oxidation degree is very low at 700 °C for the as-cast and as-forged alloys, and the weight gain are 0.075 mg/cm2 and 0.066 mg/cm2, respectively. The scratches on the surface are clearly visible. When oxidized at 800 °C, the weight gain of as-cast and as-forged alloys are 0.473 mg/cm2 and 0.413 mg/cm2, respectively. The β phase depresses with the formation of TiO2 particles on its surface, and many holes are formed at the γ phase. When oxidized at 900 °C, the weight gain of as-cast and as-forged alloys are 1.866 mg/cm2 and 1.846 mg/cm2, respectively. There is a mixed product of the Al2O3 and TiO2 on the surface, and the TiO2 grows in the outer layer of Al2O3, but the Al2O3 layer is not completely covered by TiO2. The structure of the oxide film is TiO2 layer/Al2O3 layer/TiO2+Al2O3 layer/Nb + Mn + Cr riched layer. During the oxidation process, the β phase in the sub-surface layer decomposes. Oxygen diffuses into the alloy and promotes the phase transformation of β/B2→α2. The morphology and distribution of the β/B2 phase in the as-forged alloy limits the diffusion of oxygen into the alloy, and the more uniform grain distribution makes the distribution of oxide particles more uniform, enhancing the oxidation resistance.